1982
DOI: 10.1148/radiology.144.1.7089242
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of deep fat masses in multiple symmetrical lipomatosis.

Abstract: Deep fat masses were evaluated by computed tomography (CT) in 15 patients with multiple symmetrical lipomatosis. In 4 patients, peritracheal accumulations of fat were observed. In 3 of them, tracheal compression by lipomatous tissue was demonstrated: 2 were asymptomatic and the third had severe respiratory insufficiency secondary to blockage of the airway by the vocal cords as the result of recurrent nerve palsy. In 6 patients, lipomatous tissue occupied the potential space between the spinal scapulae and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
5

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 0 publications
1
26
0
5
Order By: Relevance
“…MSL has been classified as type I (for some authors the real Madelung's disease) characterized by masses distributed in the upper half of the body, weight loss and possible deep accumulation of adipose tissue (ie, mediastinal), and type II which is more difficult to differentiate from simple obesity with diffuse involvement, weight gain and the absence of deep involvement. 3,4 The two cases reported here can be classified in the type I group. They are associated with the same neurological manifestations, polyneuropathy and memory disorders.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…MSL has been classified as type I (for some authors the real Madelung's disease) characterized by masses distributed in the upper half of the body, weight loss and possible deep accumulation of adipose tissue (ie, mediastinal), and type II which is more difficult to differentiate from simple obesity with diffuse involvement, weight gain and the absence of deep involvement. 3,4 The two cases reported here can be classified in the type I group. They are associated with the same neurological manifestations, polyneuropathy and memory disorders.…”
Section: Discussionmentioning
confidence: 83%
“…The polyneuropathy affects the cases with MSL as mentioned by other authors. [4][5][6][7][8] It may appear as an autonomic, sensory or motor neuropathy with proximal predominance, and may be associated with neuropathic skin lesions and Charcot's arthropathy. 9 Neuropathy is a frequent complication of alcoholism but many publications distinguish polyneuropathy in MSL patients from alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…Over 300 adult cases are reported in the literature with an age range of 20-71 years. The early literature on MSL was dominated by research on alcoholic men with a reported incidence of 1/25 000 in the Italian population [35] . Non-alcoholics and women are also affected [36][37][38] ; two cases have been reported in children [39,40] .…”
Section: Multiple Symmetric Lipomatosis (Madelung's Disease/syndrome;mentioning
confidence: 99%
“…Thus, in Type 1, intramediastinal localization might originate a vena cava syndrome and tracheal compression. [7] It might present also a slight decrease in cervical amplitude, intertrigo folds, and clothing discomfort, in addition to metabolic complications and disorders related to chronic alcoholism. In our case, blood urea and cholesterol levels as well as liver tests were normal, and the patient did not have any history of alcoholism and was devoid of complications of alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%